An Integrated Model to Improve Job Satisfaction: A Case for a Sustainable Construction Industry - Qasim Hussain Khahro, Qasim Hussain Khahro; Noor Yasmin Zainun, Noor Yasmin Zainun; Shabir Hussain Khahro, Shabir Hussain Khahro; Basel Sultan, Basel Sultan (Mdpi, 2023)
In the last few years, the fields of management, social psychology, and business operations have all paid a large amount of attention to the academic idea of job satisfaction. This paper looks at more than a decade of research into what makes people happy at work and what happens to them as a result. Companies have started to realize that their employees are their most valuable asset in this time of rapid change. There is no specific model of the job satisfaction of construction workers in developing countries. Thus, this paper evaluates the different job satisfaction models and also proposes an integrated job satisfaction model for construction industry workers. The data were collected from experts in the construction industry using a questionnaire survey and almost 290 experts participated in this research to assist in the development of the model. The data were analyzed using SPSS. The model was developed and validated using Smart PLS. Eight key aspects were found to be very important to improving the job satisfaction of construction workers in developing countries. Job compensation packages given to construction workers, work–life balance, career growth, and job security are the top key features investigated in this study. It is concluded that satisfied and motivated employees are imperative for the construction business, and that this is also a key factor that separates successful companies from others. The findings of this paper contribute to UN-SDG 8 “Decent Work and Economic Growth” and UN-SDG 9 “Industry, Innovation, and Infrastructure”.